ENT 300 : Restaurant Sambal Chill’in / Nurdina Sofea Mazli ... [et al.] - Mazli, Nurdina Sofea; Mazlan, Muhammad Syafiq; Muhamad Sofian Ang, Noor Syamimie; Nasir, Nursyazana (2021)
To allow us as entrepreneur to view and evaluate the proposed business venture in an objective, critical and practical manner. When making a business plan, we can view and evaluate the detail manner. Starting a business make us realise that we need to take a lot of aspect in a serious way. We will need to examine the details starting from the basic things for example, ingredients that we use and the capital issues. We also need to identified who is our target customer, the place that will be suitable to open our restaurants and ways to market our restaurants. This allow us to improve ourselves and to get good understanding about business. We can see in a clear way what steps should we take to make a successful business.